PENERIMAAN MASYARAKAT SAMIN TERHADAP PROGRAM PEMBANGUNAN DI DESA BATUREJO, KEC. SUKOLILO, KABUPATEN PATI JAWATENGAH 2013 - Suprihatini, Taufik (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
In an effort towards the developed and developing countries or intelligent and qualified society, the government continues to socialize and to coorperate with various parties in order to facilitate the development programs that have been planned in the Government Work Plan 2013. However, to realize the development programs that have been planned is not easy, considering the multicultural Indonesian society including Samin community who lived in the Baturejo village, Pati regency, Central Java Province which have their own views and still retain cultural values and doctrines. The presence of view of the pros and cons, have impacts on the development program itself.